The extract of the immature fruit of Poncirus trifoliata induces apoptosis in colorectal cancer cells via mitochondrial autophagy - Sun-Young Kim; Ho-Keun Yi; Bong-Sik Yun; Dae-Yeol Lee; Pyung Han Hwang; Hae-Ryong Park; Min Sun Kim (Food Science and Human Wellness)
The immature fruits of Poncirus trifoliate are used as a medicine for the treatment of gastrointestinal disorders, inflammation, and allergies in East Asia. However, their effect on colon cancer cells remains unclear. We investigated the effect of the immature fruit of P. trifoliate extract on colorectal adenocarcinoma. The extract of the immature fruit of P. trifoliata inhibited the proliferation of CT-26 cells compared with untreated cells and it induced autophagy and apoptosis through the protein kinase B/mammalian target of rapamycin and 5′-AMP-activated protein kinase pathways. The number of autophagic vacuoles and autophage markers increased in response to the extract. At later time-points, apoptosis increased dose/time-dependently. In CT-26 cells pre-treated a pan-caspase inhibitor prior to P. trifoliata immature fruit extract treatment, we did not find any change in pro-caspase 3 and pro-PARP levels. Additionally, in cells pre-treated autphage inhibitor, SQSTM1/p62 and LC3AB, pro-caspase 3 and pro-PARP levels did not change. Our results indicate the molecular mechanisms that the extract of the immature fruit of P. trifoliata induces apoptosis in colorectal carcinoma cells by inducing mitochondrial autophagy. In this study, we provided a draft for further investigate the use of MEPT for colorectal cancer inhibition.